Observations of coincident EMIC wave activity and duskside energetic electron precipitation on 18–19 January 2013. Issue 14 (30th July 2015) - Blum, L. W.; Halford, A.; Millan, R.; Bonnell, J. W.; Goldstein, J.; Usanova, M.; Engebretson, M.; Ohnsted, M.; Reeves, G.; Singer, H.; Clilverd, M.; Li, X.
Abstract: Electromagnetic ion cyclotron (EMIC) waves have been suggested to be a cause of radiation belt electron loss to the atmosphere. Here simultaneous, magnetically conjugate measurements are presented of EMIC wave activity, measured at geosynchronous orbit and on the ground, and energetic electron precipitation, seen by the Balloon Array for Radiation belt Relativistic Electron Losses (BARREL) campaign, on two consecutive days in January 2013. Multiple bursts of precipitation were observed on the duskside of the magnetosphere at the end of 18 January and again late on 19 January, concurrent with particle injections, substorm activity, and enhanced magnetospheric convection. The structure, timing, and spatial extent of the waves are compared to those of the precipitation during both days to determine when and where EMIC waves cause radiation belt electron precipitation. The conjugate measurements presented here provide observational support of the theoretical picture of duskside interaction of EMIC waves and MeV electrons leading to radiation belt loss. Key Points: EMIC waves and MeV electron precipitation are observed at the same UT and MLT EMIC wave and precipitation timing, extent, and drivers are examined Results provide observational confirmation of duskside EMIC‐electron interactions